DEGREES OF PUTREFACTION- A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2022)
Determination of time since death is one of the primary objective of medicolegal autopsy. This objective attains still higher importance if the dead body belongs to an unknown person or is else recovered under suspicious circumstances at strange locations where the deceased might not be expected otherwise. In addition to eye witness testimony, circumstantial evidence, degree of putrefaction of the body is one of the major criterion for determination of time since death. Plenty of data is available on rate of putrefaction in light of various post mortem changes fixing post-mortem interval for appearance or disappearance of various parameters. In this case report we report 2 cases where 2 bodies were recovered in almost similar circumstances presented with different degrees of putrefaction. The findings in this case stresses on the fact that even though post mortem interval as well as medium of submersion was same in two cases still they shows different degrees of putrefaction. Thus, opinion on time since death based on putrefactive changes should be guarded.
Keywords: Drowning; Time since death; Case report